Choice of norm for evaluating trade-off solutions in multi-criteria optimisation problems in the control of complex objects - Żak, Bogdan (Zielona Góra: Uniwersytet Zielonogórski)
When formulating multi-criteria optimisation tasks, there are two important problems to consider. The first is the selection of a number of sub-criteria such that their importance, number, and order correspond to the modelled decision-making situation, while the second is the choice of the solution method to ensure its optimality with respect to individual subcriteria. Therefore, the solution boils down to the search for a certain compromise that takes into account the influence of individual sub-criteria on the obtained result.
Keywords: decision making; vector criterion; polyoptimisation